Fertility transitions along the extensive and intensive margins - Daniel Aaronson; Fabian Lange; Bhashkar Mazumder (Federal Reserve Bank of Chicago, 2011)
This paper examines the fertility transition through a new lens: the extensive margin. Parents with high levels of children might substitute quality for quantity as the constraints on quality relax or those on quantity tighten. However, along the extensive margin, the quantity-quality trade-off cannot operate. At low levels of fertility, we expect quality and quantity to be essential complements. We apply these insights to a large school construction program in the American South during the early 20th century, the Rosenwald Rural Schools Initiative. We find that increased schooling opportunities lead to reductions in fertility among women with high fertility levels, while at the same time inducing higher levels of fertility among women with low levels of fertility. The magnitude of the fertility changes induced in the parent generation is, however, small compared to the changes in fertility induced by the Rosenwald intervention among women that were themselves treated by the intervention. The evidence from the Rosenwald intervention therefore suggests that changes in female opportunity costs induced by increased educational attainment might be among the most important driving forces of the fertility transition.
Keywords: C20; C23; C24; 330